Implementasi Algoritma Approximate Pada Aplikasi Paritta Suci Pada Kitab Tripitaka Berbasis Android - Mei Indah Trinanci Siahaan (JURIKOM (Jurnal Riset Komputer), 2019)
The word Paritta in Paliatau Pirit, literally means "full of protection". Buddhas on various occasions with the holy pali language compose Paritta or Pirit, there must be a misunderstanding that equates Paritta as a mysterious blessing or mantra, but actually there are genuine advocates that are ethical and contain philosophical values from Buddhism, which are related to aspects of the Dhamma. And the Tripitaka is a Buddhist scripture which is a collection of sermons, statements, parables, and conversations that the Buddha had done with his students and followers. Likewise with the Paritta Suci part of the Book of Tripitaka which is very necessary in the search for verses from the word Paritta Suci. Making it easier for users to read from the book. For that we need an application that can help users in translating a language that is easy to carry and can be used anytime and anywhere. The application is in the form of an android application that can be installed on a mobile phone. The book Tripitaka application requires a search process that supports the performance of the application so that the search process can shorten the time in the search itself. In this study Approximate Levensthein Distance Algorithm is an algorithm that can be used to calculate distance differences between two strings. Distance or distance is the minimum number of delete operations, insert or substitution needed to change the origin string (s) to the target string (t). And Algorithm Approximate string matching is matching strings with the basis of similarity in terms of writing (number of characters, arrangement of characters in the document). So that it can help users of the application in searching for words from the book.